PROMISING ENERGY RESOURCES OF THE FUTURE - Akhmedov Islombek; Umarov Isroil; F.Kodirova (Journal of new century innovations, 2023)
Abstract: The paper presents the results of producing hydrogen by electrolysis of water using alternative types of energy.